Climate Change and Sustainability: Challenges and Solutions for a Resilient Future - Alkhatib, Ahed J (International Journal of Alternative Fuels and Energy, 2023)
Climate change poses significant threats to global ecosystems, human health, and economic stability. This article explores the scientific basis of climate change, its environmental and social impacts, and strategies for sustainability. Emphasizing the role of renewable energy, carbon sequestration, and sustainable urban planning, the study highlights solutions to mitigate climate change and adapt to its effects. Additionally, it examines the economic and policy frameworks necessary for achieving sustainability. A sustainable future requires integrated policies, technological innovations, and global cooperation.